Blended learning : educational innovation for personalized learning : 12th International Conference, ICBL 2019, Hradec Kralove, Czech Republic, July 2-4, 2019 : proceedings /: educational innovation for personalized learning : 12th International Conference, ICBL 2019, Hradec Kralove, Czech Republic, July 2-4, 2019 : proceedings. (2019) - Unknown
No abstract available